Workload-Mediated Teacher Agency in Curriculum Adaptation: Practice-Based Evidence from Turkish Primary Schools - Ethem Gürhan (Journal of Elementary Education Research and Practice, 2026)
This study investigates primary school teachers’ curriculum adaptation practices and professional agency under workload-related constraints in Turkish primary education. Existing research has primarily examined teacher agency and curriculum enactment but has insufficiently theorized workload as a structural mediator shaping instructional decision-making. Addressing this gap, the study explores how teachers interpret and adapt curriculum expectations within demanding classroom contexts. A qualitative design was employed involving 12 public primary school teachers in central Türkiye. This study collected interview data using semi-structured protocols and analyzed them using descriptive content analysis with inductive coding. Findings indicate that curriculum adaptation is a routine, practice-based response to structural and instructional pressures. Workload, as manifested through time pressure, administrative demands, and assessment load, mediates the enactment of teacher agency, shaping pacing adjustments, content prioritization, and task redesign. Teachers deliberately orient their adaptation practices toward equity-driven instruction to sustain meaningful learning. The study reconceptualizes teacher agency as contextually bounded and workload-mediated, offering implications for curriculum policy, professional development, and workload-sensitive instructional support.